Africanfuturism and Magical Realism In Okorafor’s ‘Hello Moto’ - M. Daffa Aufa Rifqi Amran; Irana Astutiningsih; Dina Dyah Kusumayanti; Dewianti Khazanah (JENTERA: Jurnal Kajian Sastra, 2024)
This article uses the concepts of Magical Realism by Wendy B. Faris (2004) and Africanfuturism by Okorafor (2019) to analyze ‘Hello Moto’ by Nnedi Okorafor (2011). We analyzed the magical elements and concepts of African futurism in Okorafor's short stories to explain the author's intention in writing her works, which mostly use similar themes such as postcolonialism. After analyzing these two concepts, it was found that Nnedi Okorafor, through her work 'Hello Moto' reflects a postcolonial perspective on cultural hybridity by presenting advanced technology in the form of wigs and combining it with the power of black magic which can release powers such as transmission and mind control. There is a blend of Eastern and Western culture in 'Hello Moto' based on the above explanation. The contribution of this study lies in its exploration of Africanfuturism uniquely represented in Okorafor’s ‘Hello Moto’ as a medium for postcolonial discourse, showcasing how her work reimagines technological advancement through an African cultural lens while bridging traditional and modern worlds. AbstrakArtikel ini menggunakan konsep Realisme Magis oleh Wendy B. Faris (2004) dan Africanfuturisme (2019) untuk menganalisis ‘Hello Moto’ karya Nnedi Okorafor (2011). Kami menganalisis elemen magis dan konsep africanfuturisme yang terdapat di dalam cerita pendek karya Okorafor untuk menjelaskan niat penulis menulis karya-karyanya yang kebanyakan menggunakan tema yang serupa yakni tentang poskolonialisme Setelah menganalisis kedua konsep tersebut, ditemukan bahwa Nnedi Okorafor melalui karyanya ‘Hello Moto’ mencerminkan perspektif postkolonial tentang hibriditas budaya dengan menghadirkan teknologi canggih berupa wig dan memadukannya dengan kekuatan ilmu hitam yang dapat melepaskan kekuatan seperti teleportasi dan pengendalian pikiran. Terdapat perpaduan budaya Timur dan Barat dalam ‘Hello Moto’ berdasarkan penjelasan di atas. Kontribusi penelitian ini terkait dengan eksplorasi Afrofuturism sebagaimana direpresentasi dalam ‘Hello Moto’ sebagai media wacana pascakolonial, dimana kemajuan teknologi di kultur Afrika digambarkan dengan cara menjembatani dunia tradisional dan modern.